2022
DOI: 10.1038/s41598-022-17242-8
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the uncontrolled variation in the diet induced obese mouse by microbiomic characterization

Abstract: Group sizes in an animal study are calculated from estimates on variation, effect, power and significance level. Much of the variation in glucose related parameters of the diet-induced obese (DIO) mouse model is due to inter-individual variation in gut microbiota composition. In addition, standard tandem repeats (STRs) in the non-coding DNA shows that inbred mice are not always homogenic. C57BL/6NTac (B6NTac) mice from Taconic and C57BL/6NRj (B6NRj) mice from Janvier Labs were fed a high calorie diet and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…S10), also offering a possible explanation of the decreased Shannon diversity index observed in the FVT-ChP group, compared to the obese control. The chosen sample size (n = 8) group housed in two cages, is previously validated as sufficient for diet-induced obesity 95 , thereby accommodating the 3R principle of reducing the number of animals 96 . The combination of group housing and the coprophagic behaviour of the mice may cause in cage-associated effects 97 , which constitutes a limitation of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S10), also offering a possible explanation of the decreased Shannon diversity index observed in the FVT-ChP group, compared to the obese control. The chosen sample size (n = 8) group housed in two cages, is previously validated as sufficient for diet-induced obesity 95 , thereby accommodating the 3R principle of reducing the number of animals 96 . The combination of group housing and the coprophagic behaviour of the mice may cause in cage-associated effects 97 , which constitutes a limitation of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Each group was represented by 8 mice where the single animals were interpreted as the experimental unit. Decision on sample size (n = 8) was based on a previous publication where we validated the suitable sample size in measuring prediabetic symptoms by either HbA1c levels or oral glucose tolerance test (OGTT) 95 , which was further supported by a subsequent study 25 . Only male C57BL/6NTac mice were included since female mice are highly protected against diet-induced obesity 42 .…”
Section: Methodsmentioning
confidence: 99%
“…This is also offering a possible explanation of the decreased Shannon diversity index observed in the FVT-ChP group, compared to the obese control. The chosen sample size (n = 8) group housed in two cages, is previously validated as sufficient for dietinduced obesity 95 , thereby accommodating the 3R principle of reducing the number of animals in preclinical studies 96 . The combination of group housing and the coprophagic behavior of the mice may cause in cage-associated effects 97 , which constitutes a limitation of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were housed with 2 cages per group to account for potential cage effect bias. Decision on sample size (n = 8) was based on a previous publication where we validated the suitable sample size in measuring prediabetic symptoms by either HbA1c levels or oral glucose tolerance test (OGTT) 95 , which was further supported by a subsequent study 25 . Only male C57BL/6NTac mice were included since female mice are highly protected against diet-induced obesity 42 .…”
Section: Animal Model Design Of Diet-induced Obesitymentioning
confidence: 99%
“…In mice it has been shown that the same mice line from two different breeders and, thereby with essential differences in GM, respond very differently to anti-diabetic treatment (Bondarenko et al, 2022). No significant influence of sex was discovered in the weighted bacterial richness of the GM, Shannon diversity or the overall community composition.…”
Section: Discussionmentioning
confidence: 99%